2020
DOI: 10.1007/s10854-020-04360-0
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the final phase of multiphase KGdF4 materials via chemical synthesis and structural phase transition

Abstract: This study proposes a method for the final phase control of KGdF 4 crystals for the first time, based on a chemical synthesis and structural phase transition process with increased temperature. X-ray diffraction and high-resolution transmission electron microscopy were employed to characterize the resulting structures and reveal phase transition trends. Subsequently, a theoretical phase transition model was constructed. This model indicated that final products are obtained through a combination of chemical syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The partial phase transformation can be attributed to the change in pH during the preparation of the sol, from pH 7 of NP suspension to pH 2 of the final sol. Some authors reported that the nanoparticles with the formula NaLnF 4 (Ln = Gd, Y, Li) are very sensitive to pH changes [46,50]. Figure 4a shows the FTIR spectra obtained for undoped and 1.5Eu 3+ -doped NaGdF4 nanoparticles heat-treated at 450 °C for 5 h (violet and blue line, respectively) and 80SiO2-20(1.5 Eu 3+ : NaGdF4) heat-treated at 450 °C for 5 h and dried at 75 °C overnight (red and green line, respectively) in the range of 4000 cm −1 to 400 cm −1 .…”
Section: Structural Characterisation Of 80sio 2 -20(15 Eu 3+ : Nagdf ...mentioning
confidence: 99%
“…The partial phase transformation can be attributed to the change in pH during the preparation of the sol, from pH 7 of NP suspension to pH 2 of the final sol. Some authors reported that the nanoparticles with the formula NaLnF 4 (Ln = Gd, Y, Li) are very sensitive to pH changes [46,50]. Figure 4a shows the FTIR spectra obtained for undoped and 1.5Eu 3+ -doped NaGdF4 nanoparticles heat-treated at 450 °C for 5 h (violet and blue line, respectively) and 80SiO2-20(1.5 Eu 3+ : NaGdF4) heat-treated at 450 °C for 5 h and dried at 75 °C overnight (red and green line, respectively) in the range of 4000 cm −1 to 400 cm −1 .…”
Section: Structural Characterisation Of 80sio 2 -20(15 Eu 3+ : Nagdf ...mentioning
confidence: 99%